Oxford international primary science student book 5 - Roberts, Deborah (Karachi: Oxford University Press., 2024)
Oxford International Primary Science: Student Book 5 expands students' understanding of scientific concepts through engaging content and hands-on activities. Covering a range of topics including ecosystems, human biology, matter, energy, and forces, the book fosters inquiry-based learning and critical thinking skills. Each chapter includes clear explanations, experiments, and interactive exercises that encourage students to explore and apply scientific principles in real-world contexts. Designed to promote curiosity and analytical skills, this textbook lays a strong foundation for students as they progress to more advanced science studies.